Correlation between cortical morphology and synaptic-associated proteins levels in poststroke aphasia: a pilot study - Cao, Yun; Huang, Jiaqin; Zhang, Danli; Lei, Xiaojing; Tan, Zhongjian; Chang, Jingling (Frontiers in Psychology, 2025)
BackgroundPoststroke aphasia (PSA) is a leading cause of poststroke disability. The neurobiological mechanisms mediating early recovery, however, remain incompletely characterized—particularly how serum levels of key synaptic proteins correlate with neuroimaging measures of cortical integrity and collectively contribute to language outcomes. This study was therefore designed to examine the relationships between these circulating synaptic markers and structural alterations in the brain of PSA patients to elucidate the potential mechanisms underlying functional recovery.MethodsA total of 12 PSA patients and 12 healthy controls (HCs) were enrolled in this prospective study. Serum levels of synaptic-associated proteins were measured, and high-resolution 3T structural magnetic resonance imaging (MRI) was performed. Group differences in brain structure were analyzed using voxel-based morphometry (VBM) and surface-based morphometry (SBM). Correlation analysis was conducted among factors with significant group differences.ResultsCompared with HCs, PSA patients had significantly altered serum levels of α-SYN, BDNF, TrkB, CREB, and GAP-43. Voxel-wise VBM revealed decreased gray matter volume (GMV) in various regions in PSA patients, including the left postcentral gyrus (PoCG), precuneus (PCUN), superior temporal gyrus (STG), lingual gyrus (LING), inferior parietal gyrus (IPG), middle occipital gyrus (MOG), right superior parietal gyrus (SPG), and superior frontal gyrus (SFG) (uncorrected p < 0.001). According to the SBM analysis, comparisons of cortical thickness (CT) revealed significant differences between the groups in the left PCUN, inferior frontal gyrus (IFG), right posterior cingulate gyrus (PCC), etc. Furthermore, patients with PSA presented decreases in sulcal depth (SULC) in the left SFG, right inferior temporal gyrus (ITG), middle temporal gyrus (MTG), and MOG. Correlation analysis revealed significant positive correlations between the repetition score and the CT of the left Precentral Gyrus (PreCG), as well as the SPG.ConclusionIn summary, patients with PSA exhibit distinct alterations in synaptic protein expression accompanied by widespread gray matter atrophy, marked by reduced GMV, CT, and SULC, particularly in language-related regions. These structural and molecular interrelationships suggest that early recovery involves neuroplastic mechanisms, potentially mediated via synaptic plasticity as well as structural adaptation. Our findings provide novel multidimensional insights into the neurobiological substrate of PSA and highlight promising pathways for future mechanistic and therapeutic research.